2020
DOI: 10.1017/s1751731119003124
|View full text |Cite
|
Sign up to set email alerts
|

Review: Pro-inflammatory cytokines and hypothalamic inflammation: implications for insufficient feed intake of transition dairy cows

Abstract: Improvements in feed intake of dairy cows entering the early lactation period potentially decrease the risk of metabolic disorders, but before developing approaches targeting the intake level, mechanisms controlling and dysregulating energy balance and feed intake need to be understood. This review focuses on different inflammatory pathways interfering with the neuroendocrine system regulating feed intake of periparturient dairy cows. Subacute inflammation in various peripheral organs often occurs shortly befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 77 publications
0
25
0
Order By: Relevance
“…Furthermore, other studies showed that the plasma levels of most pro-inflammatory cytokines, such as TNF, IL1B, IL7, IL1RA, IL8, IL9, IL10, basic fibroblast growth factor (FGF), and other pro-inflammatory factors were increased in COVID-19. Consequently, thyme fits as an inhibitory agent of proinflammatory cytokines [51,52]. Hence, Thymus capitatus can be considered as adjuvant therapy for COVID-19 as described in the literature [53,54].…”
Section: Clinical Spectrummentioning
confidence: 99%
“…Furthermore, other studies showed that the plasma levels of most pro-inflammatory cytokines, such as TNF, IL1B, IL7, IL1RA, IL8, IL9, IL10, basic fibroblast growth factor (FGF), and other pro-inflammatory factors were increased in COVID-19. Consequently, thyme fits as an inhibitory agent of proinflammatory cytokines [51,52]. Hence, Thymus capitatus can be considered as adjuvant therapy for COVID-19 as described in the literature [53,54].…”
Section: Clinical Spectrummentioning
confidence: 99%
“…Furthermore, other studies showed that the plasma levels of most pro-inflammatory cytokines, such as TNF, IL1B, IL7, IL1RA, IL8, IL9, IL10, basic Fibroblast Growth Factor (FGF), and other pro-inflammatory factors were increased in COVID-19. Consequently, thyme fits as an inhibitory agent of pro-inflammatory cytokines [45,46]. Hence, Thymus capitatus can be considered as adjuvant therapy for COVID-19 as described in the literature [47,48].…”
Section: Clinical Spectrummentioning
confidence: 99%
“…The periparturient period, also known as the transition period, usually comprises 3 weeks pre-partum to 3 weeks post-partum and is accompanied by severe metabolic, hormonal, and immunological changes in preparation for parturition and the production of colostrum and milk (1,2). It is well established that the adequate preparations are essential for goats during the transition period to coordinate the challenges of delivery of kid, the onset of lactation, and metabolic dysfunction (3,4).…”
Section: Introductionmentioning
confidence: 99%